2011
DOI: 10.1002/srin.201100118
|View full text |Cite
|
Sign up to set email alerts
|

Study of Boronizing Mechanism of High‐Alumina Slag

Abstract: As the Al2O3 content of the iron‐making raw materials increasing, the Al2O3 content in the slag increases as well, which is the certain result in the development of the iron‐making process. Based on the slag which was from the 2# blast furnace in Hebei Qianan of China, 7 different kinds of B compositions were added. The viscosity values of the CaO ‐MgO‐Al2O3‐SiO2‐B2O3 system were measured by using the torque. The SEM and EDS apparatus were used to observe the variation characteristics of the boronizing slag of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The high value of NBO/T means the low degree of polymerization. The relation between the viscosity and NBO/T for CaO-SiO 2 Where, is the viscosity of the slag, Pa s; T is the absolute temperature, K. Here, the NBO/T is evaluated by the following formula.…”
Section: Distribution Of Bridging Oxygen and Non-bridging Oxygenmentioning
confidence: 99%
See 2 more Smart Citations
“…The high value of NBO/T means the low degree of polymerization. The relation between the viscosity and NBO/T for CaO-SiO 2 Where, is the viscosity of the slag, Pa s; T is the absolute temperature, K. Here, the NBO/T is evaluated by the following formula.…”
Section: Distribution Of Bridging Oxygen and Non-bridging Oxygenmentioning
confidence: 99%
“…For example, nowadays in China, the Al 2 O 3 content in the blast furnace slag increases by using the Australian ore fines to replace the Brazilian ore fines. The mass percentage of Al 2 O 3 in the slag is usually allowed to be lower than 15% to meet the demand of the blast furnace at present, but if the Al 2 O 3 content is higher in the final slag, the viscosity of the slag increases [1,2] , and the g g y g ( ) flowability and desulphurization ability [3,4] will decrease dramatically, causing various severe problems for the smooth and stable operation of the blast furnace. Owing to viscosity measurements are both time consuming and difficult at high temperatures, a large number of prediction models [1,[5][6][7][8][9][10][11] for viscosity have been developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a tremendous amount of slag with high Al 2 O 3 is produced during the ferronickel alloy and ferrochromium alloy production process [19][20][21]. As we know, the fluidity property of slag has a considerable influence on the smelting process and separation of metals from slag [22][23][24][25][26]. Therefore, it is vital to study the viscosity and crystallization behavior of high-alumina slag.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the little amount of B 2 O 3 remarkably improved the properties of slag [11][12][13][14][15]. Influence of B 2 O 3 on high titanium (above 20%) BF slag [11][12][13]16], medium titanium (10%-20%) BF slag [14], and high alumina (above 15%) BF slag [17,18] has been studied in previous reports. However, it is hard to find investigations on the viscous behavior of high alumina (above 15%) and medium titania (15%-20%) BF slag (HAMT BF slag) and the influence of B 2 O 3 , Al 2 O 3, and basicity on viscous behavior.…”
Section: Introductionmentioning
confidence: 99%